One-Step Synthesis of Green Fluorescent Carbon Dots for Chloride Detecting and for Bioimaging - Yue, Juan; Yu, Ling; Li, Li; Liu, Pai; Mei, Qian; Dong, Wen-Fei; Yang, Ru (Frontiers in Chemistry, 2021)
The chloride ion is an essential ion in organisms, which plays an important role in maintaining normal cell functions. It is involved in many cell activities, such as cell proliferation, cell excitability regulation, immune response, and volume regulation. Accurate detection of the chloride ion can balance its concentration in vivo, which is of great significance. In this study, we developed a green fluorescent carbon quantum dot to detect chloride concentration through the “off–on” mechanism. First, the fluorescence of carbon dots is quenched by the complex of sulfhydryl and silver ions on the surface of carbon dots. Then, the addition of chloride ions pulls away the silver ions and restores the fluorescence. The fluorescence recovery is linearly related to the concentration of chloride ions, and the limit of detection is 2.817 μM, which is much lower than those of other reported chloride probes. Besides, cell and zebrafish experiments confirmed the biosafety and biocompatibility of the carbon dots, which provided a possibility for further applications in bioimaging in vivo.